Preservasi Digital Seloko Adat Jambi, Pantun Betawi dan Berkisah Budaya Batam - Karim, Muhammad Firman; Riady, Yasir; Arisanty, Melisa; Khatib, Ahmad Juma; Ajmal, Muhammad (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Maintaining sustainability and facilitating access through digital preservation is a crucial technique for safeguarding traditional cultural heritage amid globalization and advancements in information technology. The purpose of the study is the digital preservation of three very famous but extinct oral traditions originating from three provinces in Indonesia: Seloko Adat Jambi, Pantun Betawi, and Berkisah Budaya Batam. This research method is a qualitative approach to deeply understand the phenomenon of digital preservation in a cultural context. The results of this study are that each of these traditions has significant cultural and social value for its community, but faces major challenges in its preservation, especially with rapid social and technological changes so that there needs to be an action to preserve this material so that it is easy to read and enjoyed by the community, especially young people. Through an analysis of the challenges, problems, and implications of this digitalization process, the writing in this article further identifies the factors that influence the success of digital preservation efforts, such as technological limitations, digital divides, and cultural resistance and future developments. In addition, this article also explores the potential benefits and risks of digitizing these traditions, and provides recommendations to ensure that the essence and values of culture are maintained in the digital age. The conclusion of this study emphasizes the importance of collaboration between local communities, governments, and technologists in maintaining cultural sustainability that can be enjoyed into the future.